Making public parks public: Increasing inclusivity in Denver's Civic Center Park - Bernal, Kaitlin (Kansas State University, 2017)
One of the most important aspects of a public space is its accessibility and inclusivity for all people. In urban parks, this often means that a wide variety of users must be considered during the design process. Denver Civic Center Park is a historic urban park in the heart of Denver’s downtown. The park caters to a variety of people ranging from tourist, who briefly visit the park, to people who are experiencing homelessness, and call the park home. Ensuring that the needs of people varying in age, culture, and economic background is key to any urban park’s success. Semi-structured interviews, site observations, site inventory and analysis, and critical mapping helped assess Denver’s Civic Center Park’s inclusivity and accessibility. Through a combination of improved infrastructure and additional amenities, a thoughtful redesign of the historic park addressed today’s challenges with homelessness and created a more inclusive environment. Because of the historic nature of the park only specific modifications to the southern ares were made. There are two reasons to create inclusive public spaces. The first is the social mixing that comes from people of different backgrounds and cultures sharing a safe environment. Social mixing connects groups of people through passive and active interactions that are built on seeing someone or overhearing their conversations. Social interactions, that take place in a safe environment, can trigger empathy within the community and start to build relationships between people of different socioeconomic groups. The second reason focuses on the ethics of designing public space. The infrastructure and policy of a public space should not be exclusive to a “desirable” demographic, but should include all existing users and the surrounding community. Because a large portion of users in Denver’s Civic Center Park are people experiencing homelessness, the design and programmatic amenities should consider their needs and desires. Landscape architects can influence the public’s views and the way people interact with each other by designing safe and active urban public spaces. In this project I asked, what design policies and strategies could be implemented to make Denver’s Civic Center Park more inclusive and secure for all park users, including those experiencing homelessness?
Keywords: HomelessDenver civic center park; Homelessness